Like brothers - Duplass, Mark; Duplass, Jay (Ballantine Books, 2018)
"The multitalented writers, directors, producers, and actors (The League, Transparent, Togetherness, and The Mindy Project) share the secrets of their lifelong partnership in this unique personal memoir"--